2017
DOI: 10.1097/shk.0000000000000730
|View full text |Cite
|
Sign up to set email alerts
|

The AMPK Activator Aicar Ameliorates Age-Dependent Myocardial Injury in Murine Hemorrhagic Shock

Abstract: The development of myocardial dysfunction in patients with hemorrhagic shock is significantly impacted by the patient age. AMP-activated protein kinase (AMPK) is a pivotal orchestrator of energy homeostasis, which coordinates metabolic recovery after cellular stress. We investigated whether AMPK-regulated pathways are age-dependent in hemorrhage-induced myocardial injury and whether AMPK activation by 5-amino-4-imidazole carboxamide riboside (AICAR) affords cardioprotective effects. Anesthetized C57/BL6 young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
4
14
2
Order By: Relevance
“…These data are in apparent discrepancy with our previous data demonstrating that another AMPK activator, AICAR, was able to provide beneficial effects in both young and adult male mice [20,21]. It must be noted, however, that the molecular mechanisms of metformin may extend beyond the activation of the AMPK metabolic pathway.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…These data are in apparent discrepancy with our previous data demonstrating that another AMPK activator, AICAR, was able to provide beneficial effects in both young and adult male mice [20,21]. It must be noted, however, that the molecular mechanisms of metformin may extend beyond the activation of the AMPK metabolic pathway.…”
Section: Discussioncontrasting
confidence: 92%
“…It consists of three subunits: one catalytic α-subunit, which is activated by phosphorylation, and two regulatory β- andγ subunits [14,16,40]. Consistent with our previous findings [20], we observed that there was an age-dependent dysregulation of AMPK activation in the cytosol and nuclear compartments in hearts of male mice after hemorrhagic shock. On the contrary, in female mice of both ages pAMPKα was significantly elevated in the cytosol, but not the nuclear compartment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations